First Report of Awake Craniotomy of a Famous Musician: Suprasellar Tumor Surgery of Pianist Clara Haskil in 1942 - Gasenzer, Elena Romana; Kanat, Ayhan; Neugebauer, Edmund A.M. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Clara Haskil (January 7, 1895–December 7, 1960) was one of the most famous female pianists of the 20th century. In her life and work she set new standards in piano playing. However, her career was beset by poor health and the adversities of two world wars. In her lifetime Haskil had three major disorders: juvenile scoliosis requiring treatment in her adolescence, a tumor of the sellar region requiring surgery at age 47 years, and a traumatic brain injury causing her death at the age of 65. Her medical history illustrates the development of surgical methods and rehabilitation in medicine before and after World War II. At an early age, she spent a year in a nursing home for orthopedic diseases due to scoliosis. In 1942, when she was 47 years old, she displayed the first symptoms of a suprasellar brain tumor: headache and hemianopsia. The famous surgeon Marcel David performed surgery on her without general anesthesia while Haskil mentally played a Mozart piano concerto as a neuronal representation to control her memory and mental abilities. Only 3 months after that operation she played a Mozart piano concerto at a concert that began her career as a great interpreter of Mozart. Her neurologic rehabilitation was remarkable and highlighted new methods in the field. In 1960, she traveled to Brussels for a concert. In the train station she stumbled on the stairs and hit her head on one of the steps. Skull fracture and intracranial hematoma were diagnosed. Doctors tried to operate on her but she lost consciousness and died. Haskil created new styles in piano playing, and her medical history offers indications of new concepts in neurosurgery.
Keywords: pianist; history of neurosurgery; awake craniotomy; suprasellar meningioma; traumatic brain injury